(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Throughout their economic and political histories, Armenia and China have pursued different paths in alignment with their respective regional and integration objectives. Despite lacking a common border and not being part of a single integration bloc, these countries have managed to establish and cultivate dynamic trade and economic relations. The evolution of ties with China is significantly influenced by the global One Belt One Road initiative, with numerous countries seeking to engage with this ambitious project. Armenia is no exception, and this article explores the trade and economic interactions between Armenia and China, addressing both the challenges and potential development scenarios.